Parotid Quadrantectomy Is a Safe Management for Localized Pleomorphic Adenoma - Hussein, Osama; Abdel Wahab, Khaled; Hamdy, Omar; Arafa, Mohammad; Hamed, Emad-Eldeen; Awny, Shady; Roshdy, Sameh; Denewer, Adel; Mosbah, Mahmoud (Frontiers in Surgery, 2018)
Aim: Pleomorphic adenoma is the most common benign tumor of the parotid gland and is classically treated with superficial or total parotidectomy. Less radical surgeries have been proposed to minimize the risk of facial nerve injury. The oncological safety of these procedures remains controversial. We conducted this study to evaluate the safety of superficial hemi-lobectomy (quadrantectomy). Patients & Methods: Retrospective analysis was conducted on the paraffin sections of archived superficial parotidectomy specimens from eleven male and six female patients (median age 33 years). The microscopic extent of extra-capsular extension was determined on pathological revision. In addition, prospective evaluation of twelve quadrantectomy procedures (M/F = 7/5, median age = 36y) compared to 24 radical surgeries (M=F, median age = 40y) regarding temporary and persistent facial nerve dysfunction on routine clinical assessment and recurrence rate. Results: On retrospective pathological revision, pleomorphic adenomata had a median microscopic spread of 3 mm beyond capsule in paraffin sections (SD = 3.6). On prospective analysis with a median follow-up of 33m. (range = 18-54m.), quadrantectomy had similar relative risk of temporary facial nerve dysfunction evaluated at the immediate postoperative period as well as persistent nerve dysfunction assessed at three months (P = 0.686 and P = 0.646, respectively). Of the whole study population, one case of recurrence after total parotidectomy was observed at mid-term follow-up (P = 0.400). Conclusion: parotid quadrantectomy is a safe management for smaller pleomorphic adenomata localized close to one of the two divisions of the facial nerve.